Muscle flexibility and explosive power in young artistic gymnast boys at different performance level - Siahkouhian, M.; Ebrahim, B. M.; Mehdi, M. (Science of Gymnastics Journal, 2021)
A gymnast can not succeed without enough muscle strength and endurance. The aim of this study was to determine the differences between explosive power and flexibility in young boy gymnasts at different performance levels. Ninety-five young boys who participated in this study were divided into three groups: two artistic gymnast groups (N=53) and a sedentary (N=42) group. Artistic gymnasts were classified by their performance level and sports history to an elite (E, N=15) and/or a non-elite (Ne, N=38) group. The explosive power of subjects was determined via vertical and standing long jumps. The sit and reach flexibility test was used to determine lower body muscle flexibility. Our results showed that explosive power and flexibility test records were significantly different among the three groups (P=0.001). They led to a conclusion that sport specific exercise training resulted in a concurrent improvement in explosive power and flexibility of young gymnasts.